Sources and Severity of Perceived Stress Among Iranian Medical Students - Borjalilu, Somaieh (Iran Red Crescent Med J, 2015)
BACKGROUND: Studying medicine is perceived to be stressful, and a high level of stress may have a negative effect on cognitive functioning and mental health of the students. OBJECTIVES: In this study, we assessed perceived stress and its severity, sources and determinants. PATIENTS AND METHODS: In this cross-sectional study, we assessed the perceived stress and its severity, sources and demographic variables in 341 (136 males, 205 females) randomly selected medical students of Tehran university of medical sciences, Iran, in October 2013. A self-administered valid and reliable questionnaire with a possible range of scores from 0 to 56 was used to collect the data. Stress sources were determined using logistic regression analysis. RESULTS: The overall perceived stress mean was 32.02 (SD = 5.08). Eighty-three percent of the medical students perceived stress. Students in clinical phase perceived more stress than basic sciences ones [OR 2.25, 95% CI 1.809 - 4.032]. Logistic regression analysis showed demographic (including gender and residential status), psychosocial and academic factors and the phase of study as sources of stress. CONCLUSIONS: The results of this study show that most of the medical students declared perceived stress. So, a change in medical education environment and empowering students to effectively cope with the perceived stress sources and their families to support their children is needed.